The function of the TV report on Arab satellite channels 2014 case study (Journal of the College of Basic Education, 2022)
News casts rely on all radio and television stations on the structural templates promise the most important news , Report , interview , Talk . . etc . Tv report serves as ample space with in the structure of a news bulletin to its importance in better circumstances Arab security , political and mathematically and technically .That the recipient of the Iraq whatever sex need to know the full details of any news broadcast through the media . and competent channel Aln cost one of their correspondents in digging a details of this news through the television industry professional to the report , which constitutes one – third of the news letter .The researcher of this study was divided in to several chapters , entitled methodological frame work Game to search . GS has included research problem which can be summarized to how the study of the function of the television report in the news bulletin through the study of the public . This included research on the importance and goals of the disclosure of the report function .The second chapter included a theoretical frame work has been divided researcher to two sections of this chapter are the concept of the report and its importance to our news letter .The third chapter deals with measures such as research methodology , Areas of research , Find community , search tool and building from analysis .The fourth quarter has included analysis according to the form of analysis and derive the desired results of the analysis , and perhaps most notably for Al- Arabiya a first place by (4.26%) and that all the respondents who watch the Arab satellite news watching the news reports , and by (100%) . As well as the implications of political topped the contents favored . Respondents in the reports they see and by (68.42%) . has included on the recommendations and a list of sources and a summary of the study in English .